2015
DOI: 10.1186/s40981-015-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic paravertebral block reduced the incidence of chronic postoperative pain for more than 1 year after breast cancer surgery

Abstract: BackgroundThoracic paravertebral block (TPVB) is used to reduce pain after breast cancer surgery (BCS), but the pain-reduction effects more than 1 year after surgery are unclear.FindingsFifty-one patients underwent BCS at the Niigata City General Hospital from December 2009 through March 2010. To evaluate the long-term effects of TPVB in the reduction of chronic pain after BCS, we retrospectively reviewed the anesthesia charts and medical records of these patients and conducted telephone surveys regarding post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Thoracic paravertebral block reduces many complications of epidural block in patients who have had breast surgery [3]. Studies have indicated that thoracic paravertebral block reduces the opioid consumption after breast surgery, and its effect is seen in the early postoperative period, which may be related to the anesthetic time of ropivacaine [22]. ESPB can be given unilaterally during modified radical mastectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracic paravertebral block reduces many complications of epidural block in patients who have had breast surgery [3]. Studies have indicated that thoracic paravertebral block reduces the opioid consumption after breast surgery, and its effect is seen in the early postoperative period, which may be related to the anesthetic time of ropivacaine [22]. ESPB can be given unilaterally during modified radical mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions: Dexmedetomidine as an adjunctive to ESPB can effectively relieve pain and significantly reduce the need for opioids during modified radical mastectomy for breast cancer. Trial Registration: The study was registered in the Chinese Clinical Trial Registry (ChiCTR2000031134, principal investigator: Yao Lu, date of registration: 2020- [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Early acute postoperative pain was reported to be a positive and independent predictive factor for subsequent chronic pain, 49 , 50 so our primary outcome and sample size estimation were based on PCA machine use with effective pain control 6 h after surgery. We noted that CPTP in group RD decreased, and this was similar to PCA machine use during the first postoperative 72 h compared with group S. So, dexamethasone as an adjunct is not only directed at prolonging analgesia but may also decrease the incidence of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Paravertebral block has been demonstrated to be effective in controlling postoperative pain in patients undergoing a variety of operations, and has no significant effect on hemodynamic balance, bowel movements or motor blockade. [ 17 ] The ultrason-guided paravertebral block can display the target nerve, needle as well as the adjacent anatomical structures in real time, and the application of local anesthesia can not only reduce the incidence of complications and failure rate, but also reduce the dose of local anesthesia. [ 18 ] Due to the sample number of included patients, future study is required.…”
Section: Discussionmentioning
confidence: 99%